Prevalence and characteristics of bronchiectasis in ANCA-associated vasculitis: A systematic review and meta-analysis - Yu Gu; Ting Zhang; Wenyan Zhu; Yang Han; Juhong Shi (Archives of Rheumatology, 2024)
Objectives: This systematic review and meta-analysis aimed to investigate the prevalence of bronchiectasis (BR) in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV), the association of BR with manifestations of AAV, and the features of BR in AAV. Materials and methods: PubMed, EMBASE, Web of Science, and Cochrane Library were searched for publications related to AAV and BR in English from January 1, 1994, until December 7, 2022. The prevalence of BR was synthesized using random-effects models, and sources of heterogeneity were assessed by sensitivity and subgroup analyses. Odds ratios (ORs) were calculated using fixed-effects models to evaluate the association of BR with manifestations of AAV. Only qualitative synthesis was performed on the features of BR. Results: Studies that reported on the prevalence (n=24), the association (n=6), and the features (n=8) of BR were identified. The pooled overall prevalence of BR among AAV was 19% (95% confidence interval [CI] 13-27%). The prevalence of patients with myeloperoxidase (MPO)-ANCA was significantly higher than those with proteinase 3-ANCA (28% vs. 13%, p=0.01). The female sex (OR=2.41), peripheral neuropathy (OR=4.58), MPO-ANCA (OR=4.73), and microscopic polyangiitis (OR=2.72) were associated with BR in AAV. Compared to individuals without BR, AAV-BR patients exhibited relatively lower levels of proteinuria. The diagnosis of BR could follow, be concomitant to, or precede that of AAV. However, BR usually did not respond to immunosuppressive therapy. Conclusion: AAV with BR is a common condition with special manifestations. The association of BR with AAV may not be accidental; however, the underlying pathogenesis remains to be clarified.